2005
DOI: 10.1111/j.1041-2972.2005.0022.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a predictive model of patient satisfaction with nurse practitioner care

Abstract: NPs need to be aware of developmental differences in all age groups and the differences in perceptions of care. There are many variables to consider when determining patient satisfaction with care, including the patients' sociodemographic and health variables, the healthcare system, and characteristics of the healthcare providers. Awareness of these variables may affect how NPs deliver care and ensure quality care with which the patients are satisfied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 20 publications
5
55
1
4
Order By: Relevance
“…Hayes (2007) found that patients’ age, gender, and length of acquaintance with their NPs were correlated positively with the proximal outcome of patients’ satisfaction in interviews of 103 adult patients. In contrast, Green and Davis (2005) found that patients’ age, but not patients’ gender, ethnicity, education, or income; NPs’ gender; or rural vs. urban practice setting, were associated with patients’ satisfaction in a survey of 36 NPs and 817 adult patients. The different results may be due to differences in samples, variables, methods of data collection, measures, or methods of analysis.…”
Section: Background Characteristicsmentioning
confidence: 75%
“…Hayes (2007) found that patients’ age, gender, and length of acquaintance with their NPs were correlated positively with the proximal outcome of patients’ satisfaction in interviews of 103 adult patients. In contrast, Green and Davis (2005) found that patients’ age, but not patients’ gender, ethnicity, education, or income; NPs’ gender; or rural vs. urban practice setting, were associated with patients’ satisfaction in a survey of 36 NPs and 817 adult patients. The different results may be due to differences in samples, variables, methods of data collection, measures, or methods of analysis.…”
Section: Background Characteristicsmentioning
confidence: 75%
“…Bryant and Graham (2002) described high student satisfaction with care provided by nurse practitioners in a university health setting. Green and Davis (2005) studied 348 nurse practitioners and 817 patients in various practice settings in Louisiana to identify patient characteristics that predict satisfaction. Results indicated that younger patients (18 to 25 years old) were actually less satisfied with nurse practitioner care.…”
Section: Patient Satisfaction With Nurse Practitionersmentioning
confidence: 99%
“…In North America the job was seen under the role of the Advanced Practice Nurse putting more emphasis on the medical care and the role of a nurse navigator [9][10][11]. In Israel, however, we combined both the European and the North American models of care to describe the role as the Breast Care Nurse Coordinator [12].…”
Section: Introductionmentioning
confidence: 99%